Exploring Allosteric Signaling in the Exit Tunnel of the Bacterial Ribosome by Molecular Dynamics Simulations and Residue Network Model - Guzel, Pelin; Yildirim, Hatice Zeynep; Yuce, Merve; Kurkcuoglu, Ozge (Frontiers in Molecular Biosciences, 2020)
The bacterial ribosomal tunnel is equipped with numerous sites highly sensitive to the course of the translation process. This study investigates allosteric pathways linking distant functional sites that collaboratively play a role either in translation regulation or recruitment of chaperones. We apply perturbation response scanning analysis to 700 ns long and 500 ns long coarse-grained molecular dynamics simulations of E. coli and T. thermophilus large subunits, respectively, to reveal nucleotides/residues with the ability to transmit perturbations by dynamic rationale. We also use the residue network model with the k-shortest pathways method to calculate suboptimal pathways based on the contact topology of the ribosomal tunnel of E. coli crystal structure and 101 ClustENM generated conformers of T. thermophilus large subunit. In the upper part of the tunnel, results suggest that A2062 and A2451 can communicate in both directions for translation stalling, mostly through dynamically coupled C2063, C2064, and A2450. For a similar purpose, U2585 and U2586 are coupled with A2062, while they are also sensitive to uL4 and uL22 at the constriction region through two different pathways at the opposite sides of the tunnel wall. In addition, the constriction region communicates with the chaperone binding site on uL23 at the solvent side but through few nucleotides. Potential allosteric communication pathways between the lower part of the tunnel and chaperone binding site mostly use the flexible loop of uL23, while A1336-G1339 provide a suboptimal pathway. Both species seem to employ similar mechanisms in the long tunnel, where a non-conserved cavity at the bacterial uL23 and 23S rRNA interface is proposed as a novel drug target.